Comparing the diagnosis accuracy and efficacy of presepsin (sCD14) and nCD64 in neonatal sepsis: A systematic review and meta-analysis - Amit Kumar Mittal; Mamta Patel; Dolat Singh Shekhawat; Pratibha Singh; Kuldeep Singh (Clinical Epidemiology and Global Health)
Background: Neonatal sepsis is a leading cause of morbidity and mortality among newborns, requiring early and accurate diagnosis for effective treatment. sCD14 and nCD64 have emerged as promising biomarkers due to their enhanced sensitivity and specificity compared to traditional methods. Objective: To evaluate and compare the diagnostic accuracy and clinical utility of sCD14 and nCD64 in detecting neonatal sepsis. Methods: A systematic review and meta-analysis were conducted, including studies that assessed the sensitivity, specificity, and overall diagnostic performance of sCD14 and nCD64. Various key metrics such as DOR, PLR, NLR, and AUC were analyzed. Results: Eleven studies with 1303 neonates (777 sepsis cases, 526 controls) were included. For sCD14, the pooled sensitivity was 0.82 (95 % CI: 0.65–0.92), specificity was 0.79 (95 % CI: 0.59–0.91), and AUC was 0.88. For nCD64, pooled sensitivity was 0.84 (95 % CI: 0.78–0.89), specificity was 0.79 (95 % CI: 0.65–0.88), and AUC was 0.89. Both biomarkers demonstrated high diagnostic reliability, with DORs of 18 (sCD14) and 17.04 (nCD64). Conclusions: sCD14 and nCD64 show significant potential as reliable biomarkers for the early diagnosis of neonatal sepsis. High diagnostic accuracy makes them valuable tools for improving clinical decision-making. However, further studies are needed to validate their practical implementation in routine neonatal care, feasibility, and cost-effectiveness.